Perancangan Sistem Pembelajaran Blended Learning pada Divisi Corporate Learning Bina Nusantara - Karto Iskandar; Fredy Fernanto; Mulia Gotama; Aswin Aswin (ComTech: Computer, Mathematics and Engineering Applications, 2014)
This research purpose is to design a Blended Learning System that allows participants to learning online with SCORM-based material. Tracking progress of online learning outcomes will be reported to the facilitator, management and survey work. Research methodology are method of designing and literature study. Design method using two first step in extreme methods, the planning and design programming. Literature study Methods is taken to find references on the internet and read a book for the collection of required data. The results of this study is used to simplify facilitator in acknowledging to what extent the participants understand the material provided and trigger a process of discussion in the classroom. The conclusion from this study is designed blended learning allows participants become interactive in performing learning online, showing progress and becoming interactive. Therefore, through survey, it can support learning to become more Interactive and informative.